Hydroxyapatite Nanoparticles in Drug Delivery: Physicochemistry and Applications - Sofía Lara-Ochoa; Wendy Ortega-Lara; Carlos Enrique Guerrero-Beltrán (MDPI AG, 2021)
Hydroxyapatite (HAP) has been the gold standard in the biomedical field due to its composition and similarity to human bone. Properties such as shape, size, morphology, and ionic substitution can be tailored through the use of different synthesis techniques and compounds. Regardless of the ability to determine its physicochemical properties, a conclusion for the correlation with the biological response it is yet to be found. Hence, a special focus on the most desirable properties for an appropriate biological response needs to be addressed. This review provides an overview of the fundamental properties of hydroxyapatite nanoparticles and the characterization of physicochemical properties involved in their biological response and role as a drug delivery system. A summary of the main chemical properties and applications of hydroxyapatite, the advantages of using nanoparticles, and the influence of shape, size, functional group, morphology, and crystalline phase in the biological response is presented. A special emphasis was placed on the analysis of chemical and physical interactions of the nanoparticles and the cargo, which was explained through the use of spectroscopic and physical techniques such as FTIR, Raman, XRD, SEM, DLS, and BET. We discuss the properties tailored for hydroxyapatite nanoparticles for a specific biomolecule based on the compilation of studies performed on proteins, peptides, drugs, and genetic material.